Obstructive Sleep Apnea is Associated With Adverse Maternal Outcomes Using a United States Multistate Database Cohort, 2007-2014. Issue 4 (December 2021) - Lui, B.; Burey, L.; Ma, X.; Kjaer, K.; Abramovitz, S.E.; White, R.S.
Abstract : ( Int J Obstet Anesth . 2021;45:74–82) Obstructive sleep apnea (OSA) often goes undiagnosed in reproductive-age women, affecting approximately one in ten. Due to physiological changes during pregnancy, OSA may begin or be worsened in the peripartum period. OSA is associated with higher risk of adverse events including postoperative hypoxemia and intensive care unit transfer. While some studies have linked OSA to adverse maternal outcomes, findings have been inconsistent and larger studies are needed. This study aimed to explore the association between OSA and maternal outcomes using a large US cohort.